2017
DOI: 10.1371/journal.pone.0173330
|View full text |Cite
|
Sign up to set email alerts
|

Consumer providers' experiences of recovery and concerns as members of a psychiatric multidisciplinary outreach team: A qualitative descriptive study from the Japan Outreach Model Project 2011-2014

Abstract: ObjectiveThe objective of this study was to clarify consumer providers (CPs) subjective experiences as members of a psychiatric multidisciplinary outreach team that provided services to individuals with a mental illness living in the community.MethodsA qualitative descriptive study was conducted through semi-structured interviews. Participants were clients hired as CPs in the Japanese Outreach Model Project from September 2011 until March 2014. Of the seventeen CPs, nine participated in this study. We looked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…As described in the “Nurses’ own recovery” section, the CMHNs faced themselves and managed to mature as persons by genuinely understanding themselves, resolving issues in their own lives and interpersonal relationships, and allowing for acceptance by those around them. While the participants in this study were CMHNs, professional supporters, I found similar results in other studies with peer supporters . Thus, caregivers’ own recovery experiences through their psychiatric home‐visit nursing could be a driving force to promote recovery‐oriented services.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As described in the “Nurses’ own recovery” section, the CMHNs faced themselves and managed to mature as persons by genuinely understanding themselves, resolving issues in their own lives and interpersonal relationships, and allowing for acceptance by those around them. While the participants in this study were CMHNs, professional supporters, I found similar results in other studies with peer supporters . Thus, caregivers’ own recovery experiences through their psychiatric home‐visit nursing could be a driving force to promote recovery‐oriented services.…”
Section: Discussionsupporting
confidence: 77%
“…This finding is comparable to the argument of Travelbee, who advocates similarities of experiences with patients as an important part of any nurse's ability to empathize with those they provide care for. Kido and Kayama reported that consumer providers achieved their own recovery in part by delivering care to clients. In recovery models, caregivers also make progress as individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Peer workers Flexibility Flexibility in defining peer workers’ roles [ 104 , 115 ] and in terms of the timing, structure, and frequency of sessions with service users [ 101 , 109 ] helped peer workers adapt their services to service user and community needs. Relationship Building Managing relationships with staff and service users can be a complex process due to peer workers having to shift identities from that of a service user to that of a service provider, while at the same time continuing to juggle these identities in their work [ 102 , 105 , 114 ]. Their role is to develop close trusting relationships with service users but managing boundaries and ending relationships can be emotionally complex [ 99 , 104 , 109 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“… [ 91 93 ] 3 Peer workers Innovations centred on the employment of people with lived experience of mental health problems. [ 94 104 ], [ 105 109 ], [ 110 ], [ 111 115 ] 4 Personal recovery planning New approaches to writing plans within service provider–service user encounters. [ 109 , 116 – 121 ], [ 115 , 122 ], [ 123 , 124 ] 5 Recovery colleges Education programs offering courses to service users and service providers on recovery and other topics in mental health.…”
Section: Methodsmentioning
confidence: 99%